TOPICAL ISSUES OF ANTICORRUPTION ENLIGHTENMENT AND ANTICORRUPTION EDUCATION - N. V. Shchedrin; I. A. Damm; E. A. Akunchenko (Russian Journal of Economics and Law, 2017)
Objective: to familiarize a wide range of interested persons with the results of the 2nd Siberian Anti-corruption Forum with international participation “Topical issues of anti-corruption enlightenment and anti-corruption education” held on 15-16September 2016 at the Siberian Federal University (Krasnoyarsk).Methods: in the preparation of their presentations, the forum participants used the scientific method of dialectical cognition, and a number of specific scientific methods: historical-legal, systemic-structural, comparative legal, formal logic (deduction, induction, definition and division of concepts), etc.Results: elaboration of proposals on improvement of anti-corruption enlightenment and anti-corruption education. In the forum took part the Vice-rector for social Affairs of SFU, Doctor of Economics, Professor S. I. Mutovin, Director of the Law Institute of SFU, Doctor of Law, Professor I. V. Shishko and Head of Research and Development Department of International Institute for Educational Planning, UNESCO (France), PhD in Education M. Poisson, Head of the Department of Delictology and Criminology of the Law Institute of SFU, Doctor of Law, Professor N. V. Shchedrin, Director of the Center for anti-corruption technologies (Tomsk), PhD in Law S. M. Budatarov, Head of the Center for the Russian Law Studies, Professor of the Heilongjiang University of Harbin (China), PhD in Law Pan Dunmay, Director of the Center for combating corruption and legal expertise of SFU, Associate Professor of the Deparment of Delictology and Criminology of the Law Institute of SFU, PhD in Law I. A. Damm, as well as representatives of public authorities, local governments, civil society institutions, and mass media.Scientific novelty: the forum held interdisciplinary scientific-practical discussion of the key issues of formation of public intolerance towards corruption behavior by means of anti-corruption enlightenment and anti-corruption education. Practical significance: in the ensued scientific discussion, the forum participants put forward a number of proposals for improvement of legal regulation and organization of anti-corruption enlightenment and anti-corruption education in the light of the accumulated experience, including in foreign countries.